ANALISIS KINERJA KEUANGAN DENGAN MENGGUNAKAN PENDEKATAN SHARIA CONFORMITY AND PROFITABILITY (SCnP) (Studi Kasus Bank Bukopin Syariah Periode 2021-2023) - Fauziah Laina; Sandra Dewi (CV. ADIBA AISHA AMIRA, 2025)
This research is motivated by the fluctuating financial performance of banks measured from 2021 to 2023, which can be seen from the status of the bank's liabilities and equity. This study aims to determine the level of financial performance of Bank Bukopin Syariah using the SCnP approach method for the 2021-2023 period. This study was also conducted to analyze in more depth the financial performance assessment model in Islamic banking at Bank Bukopin Syariah regarding financial performance assessment based on the Qur'an and Hadith. The method used is a qualitative method with a quantitative approach. The sample used in this study is the annual report of Bank Bukopin Syariah for the 2021-2023 period. The technique used for this study is the documentation technique. Data is taken from secondary data from the publication of the annual financial report of Bank Bukopin Syariah for the 2021-2023 period. This study describes the performance of Bank Bukopin Syariah using the SCnP method which is seen from two variables, namely the Sharia Conformity variable with the indicators of the Islamic Investment Ratio, Islamic Income Ratio, and Profit Sharing Ratio. While the Sharia Profitability variable with the indicators of ROA, ROE, and NPM. The results of the study conducted by the author show that the overall conclusion of the calculation results with the SCnP formula and associated with the table of financial performance assessment criteria sourced from Bank Indonesia Circular Letter No.9/24/DPbS/2007 shows that the financial performance of Bank Bukopin Syariah is in the unhealthy criteria, for the period 2021-2023. However, when viewed from the SCnP model table based on the bank's position in the SCnP research analysis, the results of the sharia conformity ratio and profitability are in the LRQ quadrant, which means that Bank Syariah has a high level of sharia conformity but has low profitability.